Usability Testing pada Sistem Informasi Akademik IAIN Salatiga Mengunakan Metode System Usability Scale - Mei Prabowo; Agung Suprapto (JISKA (Jurnal Informatika Sunan Kalijaga), 2021)
One of the goals of implementing a smart campus is to improve public services. Whereas the Academic Information System (Siakad) is a very important type of management information system (MIS) digital service. To find out the quality of service from the viewpoint of the user of this information system, a usability test was made. Usability is a qualitative analysis in determining the quality of an information system based on the user. The purpose of this study is to conduct usability testing SIAKAD in IAIN Salatiga using the System Usability Scale (SUS) method. Based on the usability test results, the majority of respondents use and utilize this information system well, this is proven by the value of the test results of 84,75. The evaluation results show that the Academic Information System at IAIN Salatiga is categorized as excellent.